Corneoscleroplasty with maintenance of the angle in two cases of extensive corneoscleral disease - Burk, Reinhard; Joussen, Antonia J. M. (Eye, 2000)
Purpose: We report a 2 year follow-up in two patients after corneoscleroplasty. - Method: Using lamellar corneoscleral dissection to maintain the drainage angle and its function, we performed a 14 mm allograft corneoscleroplasty in 2 eyes. For surgical treatment in both cases a 9.5 mm corneal button was excised from the recipient after peritomy and scleral lamellar preparation up to 14 mm. A 14 mm donor button was inserted and held in place with multiple Prolene sutures. One eye presented with a large perforating corneal ulcer after herpetic keratitis in a patient with recurrent rheumatoid uveitis associated with rubeosis iridis. The second eye had had a penetrating keratoplasty for keratoconus 30 years previously and presented with decompensating keratoglobus. Immune suppression was performed with systemic cyclosporin A and additional steroids when required. - Results: Both patients had a clear graft at the last follow-up visit and visual acuity was improved to a best corrected visual acuity of 0.6. Intraocular pressure in the keratoglobus eye was maintained at 6 mmHg without treatment, whereas the second case required continuing treatment with systemic acetazolamide because of neovascular glaucoma. The anterior chamber angles remained open in both patients. Contact lenses were helpful in the prevention of epithelial irregularities and defects. Both patients had an episode of immunological graft reaction which was reversed by immunosuppressive treatment. Phacoemulsification with intraocular lens implantation, which was performed 2 years after transplantation in the keratoglobus eye, did not affect the graft clarity or cause rejection episodes. - Conclusion: Our results using corneoscleroplasty have been encouraging in severe destructive corneal disease.